2018
DOI: 10.3390/fi10120118
|View full text |Cite
|
Sign up to set email alerts
|

DSP-Based 40 GB/s Lane Rate Next-Generation Access Networks

Abstract: To address the continuous growth in high-speed ubiquitous access required by residential users and enterprises, Telecommunication operators must upgrade their networks to higher data rates. For optical fiber access networks that directly connect end users to metro/regional network, capacity upgrade must be done in a cost-and energy-efficient manner. 40 Gb/s is the possible lane rate for the next generation passive optical networks (NG-PONs). Ideally, existing 10 G PON components could be reused to support 40 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…However, at >25 Gb/s bit rates, implementing PAM-4 with simple linear equalizers [7,8,17,18] to support a transmission distance of 20 km over a single-mode fiber (SMF)-as required in access networks-using only 10-G optoelectronics [7], is extremely challenging, unless higher bandwidth transmitters or receivers (e.g., 25 G photodiodes [8]), or a dedicated chromatic dispersion compensation module [4] are adopted. It has been shown that reach extension is possible by mitigating system and component nonlinearities using DSP without changing the optical infrastructure [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, at >25 Gb/s bit rates, implementing PAM-4 with simple linear equalizers [7,8,17,18] to support a transmission distance of 20 km over a single-mode fiber (SMF)-as required in access networks-using only 10-G optoelectronics [7], is extremely challenging, unless higher bandwidth transmitters or receivers (e.g., 25 G photodiodes [8]), or a dedicated chromatic dispersion compensation module [4] are adopted. It has been shown that reach extension is possible by mitigating system and component nonlinearities using DSP without changing the optical infrastructure [18,19].…”
Section: Introductionmentioning
confidence: 99%